Opportunities and risks in implementing blockchain technology as a system for financing and procurement control in the Armed Forces of Ukraine - Shramko, Oleksandr; Ostapenko, Oleksandr; Shynaiev, Denys; Bondarenko, Valeriia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
Background. In the context of war and increased inflow of international aid, Ukraine faces serious challenges in the field of defense procurement, where despite critical conditions, significant cases of corruption persist. This jeopardizes not only the efficiency of fund utilization butalso the country's reputation in the eyes of all our partners on the international stage who provide us with direct financial assistance. The use of blockchain technology can be a key solution to ensure transparency, optimize fund flow, and reduce corruption by ensuring data immutability and information transparency. The aim of this article is to analyze in detail how the implementation of blockchain can optimize financial flows and procurement control in the Armed Forces of Ukraine, and to develop specific and effective recommendations for its efficient use and implementation in conditions of armed conflict.Methods. The study applied methods of analysis and synthesis to assess the impact of blockchain technologies on the transparency of defense procurement in Ukraine. A systematic approach was used to study existing procedures and potential improvements through the implementation of blockchain.Results. The research has found that blockchain can significantly increase transparency and reduce corruption risks in procurement processes within the Armed Forces of Ukraine. Detailed analysis has shown that blockchain integration ensures the immutability of records, openaccess to transactions, and a consensus mechanism that ensures all network participants agree on the validity of records before they are added to the blockchain. This can greatly impede illegal manipulations.Conclusions. Based on the obtained data, it is recommended to implement blockchain technologies in the sphere of defense procurement. This requires the development of specialized anti-corruption measures and detailed adaptation of existing legislation for full technological integration. This involves creating solutions that take into account the specifics of military processes and ensure the highest level of security, reliability, and transparency. Further research should focus on testing, optimizing, and developing detailed blockchain systems for their effective use and implementation in conditions of military conflict.
Keywords: blockchain, smart contract, financing, procurement, Armed Forces of Ukraine, transparency, corruption